A Review on Cryoprotectant and its Modern Implication in Cryonics (Asian Journal of Pharmaceutics (AJP), 2016)
Cryoprotectants are basically some chemical compounds which prevent cells or tissues from damage due to freezing. Mostly, verification and thawing process is used in cryopreservation. The various animal tissues, organs, lymphocytes, cartilages, bone marrow, and proteins can be stored using proper cryoprotectants. Optimization of cryoprotectants is a challenging task, as elevated concentration may cause cytotoxicity. In this article, we discussed the implication, challenges, and recent advances of cryoprotectants along with its types. The importance of cryobank system and its importance were also being emphasized in this article.